Reflection on indigenous health and current challenges in dialogue with the dissertation ‘It has to be our way’: participation and protagonism of the indigenous movement in the construction of the health policy in Brazil - Krenak, Ailton (Saúde e Sociedade, 2020)
This essay presents the speech given by Ailton Krenak on March 25, 2020, at the PhD thesis’ defense of Nayara Scalco, advisee of Professor Marília Louvison, in the Graduate Program in Public Health, School of Public Health, University of São Paulo, plus excerpts from the lecture given at the International Seminar: Indigenous Health and Ecology of Knowledges in Facing Current Challenges: “It has to be our way”, on March 26, 2020. In this context, it highlights the importance of a dialogue between different knowledges and how the Indigenous Health Care Subsystem is constituted. Focusing on the debate about the relationship between the Brazilian State and indigenous peoples since colonial times, based on the production of Epistemologies of the South that guides the discussion of the dissertation, it proposes rethinking health and care beyond biomedical knowledge.